Correlação entre a circunferência do pescoço com os marcadores inflamatórios das profissionais de enfermagem do Hospital Universitário João de Barros Barreto (Belém-PA) - (:unkn) unknown (Universidade Federal do Amazonas - Universidade Federal do Pará, 2012)
This study aims to determine the correlation between neck circumference (NC) of nursing professionals, with the inflammatory markers homocysteine, fibrinogen and C-reactive protein, as well as to correlate the CP sample, with anthropometric and metabolic variables, also evaluating the socio-behavioral sample. This is a descriptive cross research, attended by 58 nursing professionals females with an age range 18-69, of a public hospital in Belém-PA, where it was carried out an anamnesis by a form, on socio-behavioral. Anthropometric variables were evaluated, such as weight, height, circumferences and bone diameters, and then sent to laboratory tests. Linear Pearson correlations indicated no significant associations between CP and biomarkers C-reactive protein (r = -0.01, P = 0.92), fibrinogen (r = -0.15, P = 0.25) and homocysteine (r = 0.03, P = 0.78). There was not strong and significant correlations between the CP and total cholesterol (r = 0.05, P = 0.69), LDL (r = 0.02, P = 0.86), HDL (r = -0.14, P = 0.27) and glucose (r = -0.12, P = 0.34), however, there were strong and significant correlations between CP and anthropometric variables such as body mass index, or BMI (r = 0.78, P <0.0001 ), waist circumference, or WC (r = 0.83, P <0.0001), percentage of body fat, or % BF (r = 0.71, P <0.0001) and percentage of muscle mass, or % MM (r = -0.62, P <0.0001). 65.5% of the sample is sedentary and 60.4% is overweight, ratified by the mean BMI (26.56 ± 4.37), CC (81.3 ± 8.93) and BF% (35 ± 6.81), 56.9% are alcohol consumers and 96.5% of PE are not smokers. Therefore, there were not significant correlations between the CP and inflammatory markers, nor with the metabolic variables in this study. However, there was strong and significant correlation with anthropometric variables. Through them, plus the laboratory tests, it is concluded that the nursing professionals of HUJBB, have strong potential for cardiovascular diseases.
Keywords: Biomarcadores; Doenças cardiovasculares; Composição corporal; Circunferência do Pescoço (CP) - Profissionais de enfermagem; Inflamatórios homocisteína; Fibrinogênio; Proteína C reativa; CIÊNCIAS DA SAÚDE